PHYSIOLOGICAL SUBSTANTIATION OF PREPARATION OF YOUTH FOR MILITARY AND PROFESSIONAL ACTIVITIES IN EXTREME CONDITIONS OF THE ARCTIC REGION - Korelskaya I.E.; Karkavtseva I.A.; Beletskaya E.V.; Blokhin N.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to verify the professional-applied physical fitness and psychophysiological status of student youth for military professional activity in the conditions of the Arctic region. Methods and structure of the study. A non-invasive method of gas-discharge visualization of induced energy emission processes based on the Kirlian effect was used. The assessment of the level of professional-applied physical fitness and indicators of energy-emission processes of the body of young people during the period of adaptation to military-professional activity in the extreme conditions of the region was made. Results and conclusions. The success of adaptation to the service of students makes high demands on the professional and applied physical and psychological training of the younger generation in the extreme conditions of the Arctic region. Three levels of adaptation to military service are proposed: basic, optimal and ultimate. The quantitative distribution of levels makes it possible to physiologically substantiate the degree of adaptation of young men to military service in the extreme conditions of the Arctic region.